Pengaruh Faktor Agent, Faktor Lingkungan Dan Faktor Pejamu Terhadap Jumlah Kasus Penyakit Tuberkulosis Di Era Pandemi Covid-19: Literatur Review - Lice Sabata; Riza Triasfitri (VISIKES: Jurnal Kesehatan Masyarakat, 2023)
In 2019 WHO determined a Global Pandemic caused by Coronavirus disease (COVID-19) which was found as many as 118,000 cases in 110 countries. So that every country is advised to prevent the spread of COVID-19 and prepare efforts to handle the spread of COVID-19 (Khoirunisa, 2021). In its development, SARS-CoV-2 underwent mutations with various variants which are now the attention of all countries in the world (Adityo Susilo, 2022). In fact, during this time the disease that often attacks the respiratory tract and spreads quite quickly, one of which is caused by the bacteria Mycobacterium tuberculosis. Indonesia is ranked 3rd in the world with 91% TB cases, namely Banten, Gorontalo, DKI Jakarta, North Ulawesi, West Sulawesi. The purpose of this literature review is to find out what factors affect the number of tuberculosis cases in the COVID-19 pandemic based on research that has been carried out.Keywords: agent factor, environmental factor, Covid-19 and TB